2016
DOI: 10.4081/rt.2017.6518
|View full text |Cite
|
Sign up to set email alerts
|

Hairy Cell Lymphoma: A Potentially Under-Recognized Entity

Abstract: Hairy cell leukemia (HCL) is a low grade B-cell lymphoproliferative disorder that typically presents with splenomegaly, cytopenias, and diffuse bone marrow infiltration. There have been few cases in the literature of HCL presenting as lymphomas in extra-nodal locations, such as soft tissues and bones without circulating leukemic cells, splenomegaly, or iliac crest bone marrow involvement. We present an additional case presenting as a thoracic mass, and discuss potential diagnostic pitfalls and management of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…However, recent reports from the era of purine analog therapy in HCL indicate that there is no difference no difference in the outcome of patients with and without bone lesions 11 . Rituximab appears to be a promising agent for relapsed patients and can be used as monotherapy or in combination with PNA 43,44 . The immunotoxin moxetumomab pasudotox and the BRAF inhibitors vemurafenib and dabrafenib have also been shown to be effective, especially in patients with limited responses to conventional therapies or treatment failure 39‐41 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, recent reports from the era of purine analog therapy in HCL indicate that there is no difference no difference in the outcome of patients with and without bone lesions 11 . Rituximab appears to be a promising agent for relapsed patients and can be used as monotherapy or in combination with PNA 43,44 . The immunotoxin moxetumomab pasudotox and the BRAF inhibitors vemurafenib and dabrafenib have also been shown to be effective, especially in patients with limited responses to conventional therapies or treatment failure 39‐41 .…”
Section: Resultsmentioning
confidence: 99%
“…In an early report, persistent pain resolution was achieved in two patients treated with RT: 60 Gy in 30 fractions or 8 Gy in a single fraction 14 . Elsewhere, pain relief was achieved by RT administered to pathologic sites to a total dose of 15 ‐ 60 Gy, 15,21,30,43 and at doses varying from 15 to 30 Gy 10 . Local RT with an “adapted” dose and fractionation schedule in the range of 20‐30 Gy has been suggested for long‐lasting symptom control 11 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rarely has HCL also presented in the form of lymphomas in bones and soft tissues [8]. A retrospective review of 37 cases by Westbrook and Golde reported that six patients had joint symptoms [9].…”
Section: Figure 4: Bone Marrow Aspirate Showing Hairy Cells (Blue Arr...mentioning
confidence: 99%
“…This presentation has been attributed to either the hematological malignancy itself or an immune dysfunction [10]. This array of varying manifestations has often led to diagnostic uncertainty and potential underdiagnosis of this malignancy [8,10]. Furthermore, various case reports have described the presentation of RA with HCL.…”
Section: Figure 4: Bone Marrow Aspirate Showing Hairy Cells (Blue Arr...mentioning
confidence: 99%